SEED TREATMENT EQUIPMENT AND THEIR ANALYSIS - Karimov Jakhongir Djumabayevich; Akramov Alisher Ashuraliyevich; Jumaniyazov Qadam (Innovate Conferences, 2025)
The quality of the prepared seed is of great importance in increasing cotton yield. Before sowing, seed treatment with chemical preparations against diseases and pests should be carried out in accordance with established regulatory and standard requirements.